Os cavaleiros do Zodíaco, recepção, sentidos e identidade: - Moreira, João Antonio Rodriguês dos Santos (2023)
This dissertation seeks to analyze the cultural consumption of the narratives present in the Japanese cartoon The Knights of the Zodiac, in the context of the city of Araguaína, under the prism of Cultural Studies. We sought to develop a research on anime and The Knights of the Zodiac, as well as to analyze the history of their production under the theoretical bias of authors, such as Stuart Hall, Raymond Williams and Douglas Kellner, among other authors and researchers who approached the object. of the research and contributed theoretically and methodologically to this investigation. Therefore, a survey was made of the main Japanese animation events existing in Brazil and Tocantins, highlighting the city of Araguaína. After that, we tried to highlight conceptions of Culture that make a bridge between the television environment, cultural practices and the existing relations between Identity and Globalization, listing a theoretical study about identity elements in post-modernity, through the consumption of experience. Subsequently, we sought to present the data obtained through focus groups held at the 2018 and 2019 Anime Sun festival in Araguaína, as well as quantitative research carried out by the Google Forms platform, thus pointing out some implications regarding cultural consumption. , aiming to highlight the way in which The Knights of the Zodiac is received.